DNA Damage Response and Repair in Adaptive Immunity - Luo, Sha; Qiao, Ruolin; Zhang, Xuefei (Frontiers in Cell and Developmental Biology, 2022)
The diversification of B-cell receptor (BCR), as well as its secreted product, antibody, is a hallmark of adaptive immunity, which has more specific roles in fighting against pathogens. The antibody diversification is from recombination-activating gene (RAG)-initiated V(D)J recombination, activation-induced cytidine deaminase (AID)-initiated class switch recombination (CSR), and V(D)J exon somatic hypermutation (SHM). The proper repair of RAG- and AID-initiated DNA lesions and double-strand breaks (DSBs) is required for promoting antibody diversification, suppressing genomic instability, and oncogenic translocations. DNA damage response (DDR) factors and DSB end-joining factors are recruited to the RAG- and AID-initiated DNA lesions and DSBs to coordinately resolve them for generating productive recombination products during antibody diversification. Recently, cohesin-mediated loop extrusion is proposed to be the underlying mechanism of V(D)J recombination and CSR, which plays essential roles in promoting the orientation-biased deletional end-joining . Here, we will discuss the mechanism of DNA damage repair in antibody diversification.